A Comparative Study on Caudal Bupivacaine with and without Tramadol for Analgesia Postoperatively in Paediatric Inguino Scrotal Surgeries - Shumaila Ashfaq, Faheem Asghar, Aftab Ahmad Channa, Muhammad Saqib, Nisar Ahmad, Shahjehan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this analysis was to govern the analgesic effect of tramadol with caudal bupivacaine in children enduring inguinal-scrotal surgery postoperatively. Study design: A Quasi experimental study. Methods: In this comparative and double-blind study, 120 children undergoing inguinal scrotal surgery were involved in the analysis. They were 2-12 years old. The inclusion standards were children from ASA I and II. The two identical groups were formed. After initiation of general anesthesia, group A patients (n = 60) 0.25% bupivacaine 0.75 ml / kg was administered and tramadol 1 mg / kg with 0.25% bupivacaine 0.75 ml / kg were administered in B group (n = 60). Postoperative pain was evaluated with a visual analogue pain score in 6-7 years of age children and with behavioural reflexion in pre-speech children. Using a 4-point sedation scale; Sedation was assessed; heart rate, mean arterial pressure, arterial oxygen saturation and respiration rate. The sedation and pain were documented at consistent duration up to 24 hours after surgery immediately after recovery from anesthesia. If the pain score was higher than 4, paracetamol (20 mg / kg) was administered rectally. Results: Addition of intravenous bupivacaine and tramadol suggestively have longer postoperative analgesia (10.1 ± 2.1 hours) in group B, while the mean duration of analgesia (2.90 ± 0.79 hours) in group A, where bupivacaine alone was, provided. No significant changes were observed in blood pressure, O2 saturation and heart rate between groups. Apart from vomiting and nausea, no side effects like retention of urine, depression and pruritus were observed. Conclusion: In children undergoing inguinal scrotal surgery, caudal bupivacaine and tramadol have more lasting and better postoperative analgesia than bupivacaine alone.